Formation of the Mechanism of Corporate Social and Environmental Responsibility of the Trading Company - CHORTOK, Yulija; YEVDOKYMOVA, Alona; SERPENINOVA, Yuliya (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.9.5(29).13, 2019)
It was determined that the impact of corporate social and environmental responsibility (CSER) on the formation of the company’s distribution policy has more integrated mechanism than previously assumed. The article emphasizes the fact that all intermediaries (major, regional, local distributors) must comply with the principles and provisions of СSER of manufacturer as the brand owner at the stage of providing consumer with the products. CSER mechanism of the trading company is suggested to form a sales management strategy for a trading company, that is developed on the basis of CSER of manufacturer and aimed at improving economic results and improving social, environmental and economic state of the territory. The conceptual foundations of the mechanism of cooperation with the local distributor are proposed and the expediency of its attraction, which is based on the analysis of the BCG matrix, is justified using Sumy affiliated branch of LLC Bayadera Logistic as case study.